Hubungan Pola Asuh Orangtua dengan Hubungan Sosial Siswa - Nofrizal Nofrizal (Universitas Negeri Padang, 2023)
This study aims to describe the parenting style, social relationships of students in SMP Negeri 13 Padang.This study uses a descriptive approach and simple linear correlation analysis. The sample of this study was 273 students. Sampling using simple random sampling technique. The instruments used were the